Kinesio taping and the circulation and endurance ratio of the gastrocnemius muscle - Stedge, H. L.; Kroskie, R. M.; Docherty, C. L. (Journal of Athletic Training, 2012)
Context: Kinesio Tex tape is a therapeutic tape that is applied with the Kinesio-taping (KT) method and is theorized to increase circulation and subsequently improve muscle function. However, little research has been conducted to determine how KT affects performance. Objective: To determine the effect of KT on muscular endurance ratio, blood flow, circumference, and volume of the gastrocnemius muscle. Design: Randomized controlled clinical trial. Setting: Research laboratory. Patients or Other Participants: Sixty-one healthy, active people (23 men, 38 women; age = 19.99 ± 8.01 years, height = 169.42 ± 23.62 cm, mass = 71.53 ± 36.77 kg) volunteered to participate. They were assigned randomly to 1 of 3 groups: treatment KT, sham KT, and control. Intervention(s): Tape was applied based on group assignment. The treatment KT group received the ankle-tape technique as described in the KT manual. The sham KT group received 1 strip of Kinesio Tex tape around the circumference of the proximal gastrocnemius muscle. The control group did not receive tape application. Main Outcome Measure(s): The dependent variables were blood flow in blood perfusion units, volume of water displacement in milliliters, circumference of the gastrocnemius muscle in centimeters, and endurance ratio in joules measured before, 24 hours after, and 72 hours after the intervention. Separate repeated-measures analyses of variance were conducted for each dependent variable. Results: We found no group-by-test day interaction for endurance ratios (F4,116 = 1.99, P = .10). Blood flow, circumference, and volume measurements also yielded no differences among groups (F2,58 range, 0.02-0.51; P > .05) or test days (F2,116 range, 0.05-2.33; P > .05). Conclusions: We found KT does not enhance anaerobic muscle function measured by endurance ratio. The KT also did not affect circulation or volume of the gastrocnemius muscle in a healthy population.